A thousand days John F. Kennedy in the White House - Schlesinger, Arthur M. 1917-2007 (Houghton Mifflin, 1965)
The Special Assistant to President Kennedy describes the historic events in which John F. Kennedy participated during his three years in the White House.
Keywords: Kennedy, John F.; Kennedy, John F <1917-1963> -- (John Fitzgerald); Kennedy, John F. -- 1917-1963; Geschichte 1960-1963; Politieke ontwikkeling; Presidenten; Geschichte; Persönlichkeit, Politik; Politisches Attentat; Staatsoberhaupt; Politik; EE. UU - Política y gobierno - 1961 1963; USA; United States -- Politics and government -- 1961-1963